An audit to evaluate the safety and efficacy of percutaneous endoscopic gastrostomy placement in patients with learning disabilities. (19th June 2014) - Ayres, Lachlan; Black, Chris; Scheepers, Mark; Shaw, Ian
<x xml:space="preserve">Abstract</x> Accessible Summary Patients with severe learning disabilities may lose weight and become malnourished for a variety of reasons. Insertion of a feeding tube through the abdomen, directly into the stomach can provide a reliable and permanent route for nutrition to be delivered. Our study of 42 patients has shown that in every case the procedure was performed following a team based assessment of each patient, as is recommended by national advisory groups. We found that the procedure is generally very safe but can require a general anaesthetic. However, complications relating to problems with the feeding tube were very common, and some patients did not gain weight. It is unclear from the literature what effect this intervention has on quality of life and we did not assess this in our study. Summary Percutaneous endoscopic gastrostomy insertion is an effective method of providing enteral nutrition to patients with neurologically unsafe swallowing or failure of feeding. Patients with severe learning disabilities may develop unsafe swallowing and benefit from percutaneous endoscopic gastrostomy placement. It is unclear whether this intervention improves quality of life. We aimed to describe the efficacy and safety of percutaneous endoscopic gastrostomy insertion in patients with learning disabilities and determine whether multidisciplinary team assessment occurred as per British Society of Gastroenterology recommendations. We performed a retrospective case note audit of 42 patients with severe learning disabilities who underwent percutaneous endoscopic gastrostomy insertion. Forty two patients underwent 117 procedures: 38 index percutaneous endoscopic gastrostomy insertions, 43 percutaneous endoscopic gastrostomy replacements, 35 percutaneous endoscopic gastrojejunostomy replacements and 1 percutaneous endoscopic gastrostomy removal [six procedures (5.1%) were unsuccessful]. General anaesthetic was required for 34 (29%) procedures. Mean weight pre‐percutaneous endoscopic gastrostomy was 39.8 kg and mean weight after a median follow‐up of 21.5 months was 46.1 kg (mean weight gain = 2.3 kg). Thirty day mortality was zero. Complications were common (74%) and included perforation n = 1, aspiration pneumonia n = 13, tube displacement n = 10, and percutaneous endoscopic gastrostomy site infection n = 4. In two cases of unsuccessful percutaneous endoscopic gastrostomy insertion, surgical feeding gastrostomy was required. Ongoing vomiting occurred in six patients (14.3%) prompting conversion to percutaneous endoscopic gastrojejunostomy in five cases. A best interests meeting or multidisciplinary team assessment occurred for all patients. In this cohort, percutaneous endoscopic gastrostomy placement appears to be safe and results in a modest weight gain. Complications occur in the majority. Percutaneous endoscopic gastrojejunostomy should be considered for those with ongoing vomiting.